miR-125a Promotes the Progression of Giant Cell Tumors of Bone by Stimulating IL-17A and β-Catenin Expression - Hua Jin; Dian-Wei Li; Shu-Nan Wang; Song Luo; Qing Li; Ping Huang; Jian-Min Wang; Meng Xu; Cheng-Xiong Xu (Elsevier, 2018)
Giant cell tumors of bone (GCTBs) exhibit high recurrence and aggressive bone lytic behavior; but, the mechanism of GCTB progression is largely unknown. In GCTB, we detected abundant levels of miR-125a, which were associated with tumor extension, grade, and recurrence. miR-125a stimulates stromal cell tumorigenicity and growth in vivo by promoting the expression of interleukin-17A (IL-17A) and β-catenin. In contrast, inhibition of miR-125a suppressed stromal cell tumorigenicity and growth. Then, we found that miR-125a stimulates IL-17A by targeting TET2 and Foxp3, and it stimulates β-catenin expression by targeting APC and GSK3β in stromal cells. Furthermore, we identified that IL-17A stimulates miR-125a by activating nuclear factor κB (NF-κB) signaling in stromal cells. Finally, our data show that simultaneous inhibition of IL-17A signaling and miR-125a more significantly inhibits stromal cell growth than miR-125a inhibition alone. miR-125a stimulates the progression of GCTB, and it might represent a useful candidate marker for progression. Simultaneously blocking miR-125a and IL-17A might represent a new therapeutic strategy for GCTB. Keywords: miR-125a, GCTB, recurrence, IL-17A, β-catenin signaling